Olivine-rich asteroids in the near-Earth space. Issue 2 (15th March 2018) - Popescu, Marcel; Perna, D; Barucci, M A; Fornasier, S; Doressoundiram, A; Lantz, C; Merlin, F; Belskaya, I N; Fulchignoni, M
Abstract: In the framework of a 30-night spectroscopic survey of small near-Earth asteroids (NEAs), we present new results regarding the identification of olivine-rich objects. The following NEAs were classified as A-type using visible spectra obtained with 3.6-m New Technology Telescope: (293726) 2007 RQ17, (444584) 2006 UK, 2012 NP, 2014 YS34, 2015 HB117, 2015 LH, 2015 TB179, 2015 TW144. We determined a relative abundance of $5.4\hbox{ per cent}$ (8 out of 147 observed targets) A-types at a 100-m size range of NEA population. The ratio is at least five times larger compared with the previously known A-types, which represent less than ${\sim }1\hbox{ per cent}$ of NEAs taxonomically classified. By taking into account that part of our targets may not be confirmed as olivine-rich asteroids by their near-infrared spectra, or they can have a nebular origin, our result provides an upper-limit estimation of mantle fragments at size ranges below 300 m. Our findings are compared with the 'battered-to-bits' scenario, claiming that at small sizes the olivine-rich objects should be more abundant when compared with basaltic and iron ones.